Evidence for the emergence of leg sympathetic vasoconstrictor tone with age in healthy women. Issue 1 (27th January 2015) - Moore, David J.; Barlow, Matthew A.; Gonzales, Joaquin U.; McGowan, Cheri L.; Pawelczyk, James A.; Proctor, David N.
Abstract: While muscle sympathetic nerve activity (MSNA) is elevated with advancing age, correlational evidence suggests that, in contrast to men, basal MSNA is not related to resting lower limb hemodynamics in women. However, limited data exists in women that have attempted to directly assess the degree of limb sympathetic vasoconstrictor tone, and whether it is altered with age. To address this issue, we measured changes in femoral artery vascular conductance (FVC) during an acute sympatho‐inhibitory stimulus (−60 mm Hg neck suction, NS) in groups of healthy younger ( n  = 8, 23 ± 1 years) and older ( n  = 7, 66 ± 1 years) women. The percent change in FVC in response to NS was significantly augmented in the older ( P  = 0.006 vs. young) women. Although NS caused no significant change (3 ± 3%, P  = 0.33) in FVC in the young women, there was a robust increase in FVC (21 ± 5%, P  = 0.003) in the old women. Collectively, these findings provide evidence that in women, leg sympathetic vasoconstrictor tone emerges with age. Abstract : e12275 In the present study, we sought to compare the amount of sympathetic vasoconstriction in the resting lower limbs (i.e., legs) of younger and older women. Leg (femoral artery) vascular conductance increased in older but not younger women during an acute sympatho‐inhibitory stimulus. These findings suggest that in women there is an emergence of lower limb sympathetic vasoconstrictor tone with advanced age.